Penerapan Terapi Bermain Puzzle dengan Terapi Getar dalam Meningkatkan Fungsi Motorik Halus Anak dengan Cerebral Palsy Usia Pra Sekolah - Hartimang, Hartimang; Suryani, Yayat; Ummu, Dewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effectiveness of applying puzzle play therapy and vibration therapy in improving the fine motor function of preschool children with cerebral palsy. The research method used is a quasi-experimental, pre-post-test control group design. The study's results showed that the average fine motor skills of CP children before the intervention was 20.26, and after the intervention, it was 16.16. In the control group, before the intervention, it was 20.26; after the intervention, it was 18.95; the decrease in value indicates motor skills heading towards better. Applying puzzle play therapy and vibration therapy improves the fine motor function of preschool cerebral palsy children (p-value 0.001). In conclusion, puzzle therapy improves the fine motor function of preschool preschool cerebral palsy children more than vibration/vibration therapy. Keywords: Puzzle Play, Cerebral palsy, Fine Motor, PreschoolPreschool, Vibration Therapy